I-Wire Heart-on-a-Chip I: Three-dimensional cardiac tissue constructs for physiology and pharmacology. (15th January 2017) - Sidorov, Veniamin Y.; Samson, Philip C.; Sidorova, Tatiana N.; Davidson, Jeffrey M.; Lim, Chee C.; Wikswo, John P.
Graphical abstract: Abstract: Engineered 3D cardiac tissue constructs (ECTCs) can replicate complex cardiac physiology under normal and pathological conditions. Currently, most measurements of ECTC contractility are either made isometrically, with fixed length and without control of the applied force, or auxotonically against a variable force, with the length changing during the contraction. The "I-Wire" platform addresses the unmet need to control the force applied to ECTCs while interrogating their passive and active mechanical and electrical characteristics. A six-well plate with inserted PDMS casting molds containing neonatal rat cardiomyocytes cultured with fibrin for 13–15 days is mounted on the motorized mechanical stage of an inverted microscope equipped with a fast sCMOS camera. A calibrated flexible probe provides strain load of the ECTC via lateral displacement, and the microscope detects the deflections of both the probe and the ECTC. The ECTCs exhibited longitudinally aligned cardiomyocytes with well-developed sarcomeric structure, recapitulated the Frank-Starling force-tension relationship, and demonstrated expected transmembrane action potentials, electrical and mechanical restitutions, and responses to both β-adrenergic stimulation and blebbistatin. The I-Wire platform enables creation and mechanical and electrical characterization of ECTCs, and hence can be valuable in the study of cardiac diseases, drug screening, drug development, and the qualification of cells for tissue-engineered regenerative medicine. Statement of Significance: There is a growing interest in creating engineered heart tissue constructs for basic cardiac research, applied research in cardiac pharmacology, and repair of damaged hearts. We address an unmet need to characterize fully the performance of these tissues with our simple "I-Wire" assay that allows application of controlled forces to three-dimensional cardiac fiber constructs and measurement of both the electrical and mechanical properties of the construct. The advantage of I-Wire over other approaches is that the constructs being measured are truly three-dimensional, rather than a single layer of cells grown within a microfluidic device. We anticipate that the I-Wire will be extremely useful for the evaluation of myocardial constructs created using cardiomyocytes derived from human induced pluripotent stem cells.